Knowledge, Awareness and Practices Regarding Dengue Fever among the Rural and Urban Populations of Salem District - Mohamed Yasir Arafath (Journal of Global Pharma Technology, 2019)
Objective: The objectives of the study were to assess how many people have knowledge and level of awareness on dengue, to know about most prevalent preventive measure, to ascertain the source of information regarding dengue and to enquire about the diagnostic measures and treatment strategies used by affected individuals.Methods: A cross-sectional observational study was conducted on 1000 respondents in Rural and Urban areas of Salem district, Tamilnadu to evaluate the knowledge, awareness and practices regarding dengue fever.Results: The results showed that only 52% of the rural respondents and 96% of urban respondents were aware about dengue fever.53% of the rural respondents and 97% urban respondents identified the vector as mosquito. The overall knowledge of dengue specific symptoms was much lower, in rural as compared to urban areas. The knowledge about the preventive measures was inadequate among the rural respondents when compared to that of urban respondents. Majority of the rural respondents (30%) had no source of information about dengue fever. While among the urban respondents, 29% had information about dengue fever from T.V/radio.Conclusion: The overall knowledge, awareness and practices regarding dengue fever were found to be inadequate among the rural populations when compared to urban populations. There is a need to make rural people aware of different preventive practices and reduce this knowledge application gap.Keywords: Dengue Fever; Knowledge; Awareness; Practices; Rural; Urban